If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6f + 13 = -7f + -65 Reorder the terms: 13 + 6f = -7f + -65 Reorder the terms: 13 + 6f = -65 + -7f Solving 13 + 6f = -65 + -7f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '7f' to each side of the equation. 13 + 6f + 7f = -65 + -7f + 7f Combine like terms: 6f + 7f = 13f 13 + 13f = -65 + -7f + 7f Combine like terms: -7f + 7f = 0 13 + 13f = -65 + 0 13 + 13f = -65 Add '-13' to each side of the equation. 13 + -13 + 13f = -65 + -13 Combine like terms: 13 + -13 = 0 0 + 13f = -65 + -13 13f = -65 + -13 Combine like terms: -65 + -13 = -78 13f = -78 Divide each side by '13'. f = -6 Simplifying f = -6
| graphx+2y=-7 | | 2b+3=9 | | 12x^2-x-35= | | 28=12+y+3y | | 50+3.75x=800 | | -14r=-4r-50 | | 50+3.75x=400 | | -40-9x=13x+72 | | 9x^2+18x-27= | | 8t^2+32t+24= | | 45-3s=-6s | | 7m=56 | | a+4=7 | | 2x=10-2y | | 4k^2+2k-12= | | x^2-1.5x+5=0 | | 2r^2+3r-14= | | 2n^2-11n+13= | | 50+3.75x=50 | | 18v^2+24v+12= | | 5x=x-48 | | 50+3.75=50 | | g(x)=3x^2-8+5 | | 69=7v-6 | | 6p^2=-31p-5 | | 1-m=1 | | 6y^2+2y-2= | | 5x^2-17x+14= | | 3(2x-7)= | | 10x^2-20xy+10y^2= | | k-3= | | 3(1-4)x=2(-4x+7) |